The Bloomsbury companion to language industry studies - Angelone, Erik; Ehrensberger-Dow, Maureen; Massey, Gary (Bloomsbury Academic, 2020)
"This volume provides a comprehensive overview of the key issues shaping the language industry, including translation, interpreting, machine translation, editing, terminology management, technology and accessibility. By exploring current and future research topics and methods, the Companion addresses language industry stakeholders, researchers, trainers and working professionals who are keen to know more about the dynamics of the language industry. Providing systematic coverage of a diverse range of translation and interpreting related topics and featuring an A to Z of key terms, The Bloomsbury Companion to Language Industry Studies examines how industry trends and technological advancement can optimize best practices in multilingual communication, language industry workspaces and training"--Bloomsbury Collections
Includes bibliographical references and index
Keywords: Übersetzungsbüro; Translating services; Language and languages / Economic aspects; Translating and interpreting; Language and languages; Economic aspects; Aufsatzsammlung